Prognostic value of right ventricular echocardiographic measures in patients with heart failure with reduced ejection fraction. Issue 9 (2nd August 2021) - Lundorff, Ingrid Josefine; Sengeløv, Morten; Pedersen, Sune; Modin, Daniel; Bruun, Niels Eske; Fritz‐Hansen, Thomas; Biering‐Sørensen, Tor; Godsk Jørgensen, Peter
Abstract: Purpose: Right ventricular (RV) dysfunction is associated with poor outcome in patients with heart failure. In order to better predict mortality in this patient group we wanted to compare the prognostic value of conventional and advanced RV echocardiographic measures. Methods: Echocardiographic examinations were retrieved from 701 patients. End point was all‐cause mortality and follow‐up 100%. RV parameters were measured offline in accordance with current guidelines. Speckle tracking was derived using the algorithm originally designed for the left ventricle. Results: During follow‐up (median: 39 months) 118 patients (16.8%) died. RV global longitudinal strain (GLS) and RV free wall strain (FWS) remained associated with mortality after multivariable adjustment independent of Tricuspid annular plane systolic excursion (TAPSE) (RV GLS: HR 1.07, 95%CI 1.02–1.13, p = 0.010, per 1% decrease) (RV FWS: HR 1.05, 95%CI 1.01–1.09, p = 0.010, per 1% decrease). This seemed to be caused by significant associations in men. All RV estimates provided prognostic information incremental to established risk factors and significantly increased C‐statistics. Conclusions: RV GLS and FWS were associated with mortality in HFrEF patients after multivariable adjustment independent of TAPSE. TAPSE, however, remained as the strongest prognosticator in women. More research is needed to identify whether speckle tracking could be superior to conventional RV measures in identifying HFrEF patients with poor outcome.